(untitled) (Research, Society and Development, 2022)
Introduction: Modifications occurred at Obstetrics Service of Euryclides de Jesus Zerbini Hospital, in São Caetano do Sul, arising from the insertion of students from the medical school at the Municipal University of São Caetano do Sul, changing the routine of the health team, generating the need to identify problems and solutions. Objective: To analyze the perception of the actors about the insertion of the interns of the Medicine Course, in the care processes at the Hospital. Method: Qualitative study, , using a convenience sample of students from the 9th semester, patients/family members assisted by students, staff in contact with students and doctors/preceptors/professors of the course, totaling 4 groups. Result: Unpreparedness was observed in the reception of students, in the identification and presentation to the team, patients/family members, and also a deficit in the integration with the team and service. The preceptors weren’t trained to perform the preceptorship. There was discomfort on the part of the team due to the presence of the inmates; patients’ estrangement due to lack of knowledge of the hospital’s academic characteristics; unpreparedness of preceptors to welcome and guide them and a feeling of lack of belonging among inmates in the service due to lack of integration. Conclusion: The disruption of in-service practice activities in the study can harm training, quality of care and organizational climate. The findings encourage the review of the integration processes between the university and the service studied, employees, users and students, as well as the development of training strategies for preceptors by the university to improve teaching and practice in service to students of the university’s undergraduate course.